Group Dynamics in Entrepreneurial Team Formation - a Case Study - Popovics, Péter; Katonáné Kovács, Judit; Árváné Ványi, Georgina; Gál, Tímea (Marketing & Menedzsment, 2017)
AIMS OF THE PAPER In 2010 the innovative Finnish Fligher Education model (Tiimiakatemia - Team Academy) was launched at the University of Debrecen. In this system, team entrepreneurs - that is, individuals who have to work together in teams - are developed. In this particular study the authors attempt to analyse how this model can be used in a Team Entrepreneur Education system to build high performing teams and also to determine which tools are best able to enhance its efficiency. METHODOLOGY The methods used were in-depth interviews together with a review of the authors’ own experiences in the form of a case study. In total, 44 students and 10 team coaches were interviewed. RESULTS The respondents recommended the adoption of a Personal Learning Contract (a coaching tool) in Higher Education and also in Team Formation. One-and-a-half years were not enough for the creation of high performance teams, and so for this form of education the study period must be longer. RECOMMENDATIONS The use of the Personal Learning Contract may be an answer to the challenges outlined in the literature, and the efficient and effective support of the team coach is necessary if the teams are to be able to complete each phase successfidly.